Safety and immunogenicity of 15-valent pneumococcal conjugate vaccine (PCV15) in healthy infants. Issue 45 (29th October 2018) - Greenberg, David; Hoover, Patricia A.; Vesikari, Timo; Peltier, Christopher; Hurley, David C.; McFetridge, Richard D.; Dallas, Michael; Hartzel, Jonathan; Marchese, Rocio D.; Coller, Beth-Ann G.; Stek, Jon E.; Abeygunawardana, Chitrananda; et al.
Abstract: Background: Pediatric use of pneumococcal conjugate vaccines (PCV) has been associated with significant decrease in disease burden. However, disease caused by non-vaccine serotypes has increased. Safety and immunogenicity of 15-valent PCV (PCV15) containing serotypes included in 13-valent PCV (PCV13) plus serotypes 22F and 33F were evaluated in infants (NCT01215188). Methods: Infants received adjuvanted PCV15, nonadjuvanted PCV15, or PCV13 at 2, 4, 6, and 12–15 months of age. Safety was monitored for 14 days after each dose. Serotype-specific IgG geometric mean concentrations (GMCs) and opsonophagocytic activity (OPA) geometric mean titers (GMTs) were measured at postdose-3, predose-4, and postdose-4. Results: Safety profiles were comparable across vaccination groups. At postdose-3, both PCV15 formulations were non-inferior to PCV13 for 10 of 13 shared serotypes but failed non-inferiority for 3 serotypes (6A, 6B, and 19A) based on proportion of subjects achieving IgG GMC ≥0.35 µg/mL. Adjuvanted PCV15 and nonadjuvanted PCV15 were non-inferior to PCV13 for 11 and 8 shared serotypes, respectively, based on postdose 3 comparisons of GMC ratios. PCV15 induced higher antibodies to serotypes 3, 22F, and 33F than PCV13. Conclusions: PCV15 displayed acceptable safety profile and induced IgG and OPA to all 15 vaccine serotypes at levels comparable to PCV13 for 10 of 13 shared serotypes. Study identification: V114-003. CLINICALTRIALS.GOV identifier: NCT01215188.